Jelly Candy Hydroxyapatite from Mackerel Fish Bone - Lia Anggresani; Santi Perawati; Ryan Afandi; Rahmadevi (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Calcium is a mineral that is needed by bones and teeth. Calcium needs have not been achieved evenly among children, about 1000mg/day. Hydroxyapatite contains Ca and apatite which is good for the maintenance of bones and teeth. Hydroxyapatite is made from the bones of mackerel, where the bones of mackerel have a high source of calcium. For easy being consumed for children, the hydroxyapatite made in the form of jelly candy. Objective: The aim of this research was Hydroxyapatite Mackerel Fish Bone can be made as Jelly Candy. Methods: Hydroxyapatite from mackerel bones is made by the precipitation method. Then, hydroxyapatite was formulated into jelly candy with concentrations of hydroxyapatite was 18%, 19% and 20% respectively for Formula I, II and III. Jelly candy evaluation includes organoleptic test, gel strength, khamir and ALT ochre, weight uniformity, pH, hedonics, homogeneity and storage. Results: The evaluation showed that all jelly candy formulas are safe for consumption according to SNI 3547.2-2008. Conclusion: In conclusion, hydroxyapatite mackerel fish bone can be made as Jelly Candy with the best concentration in Formula 1.